Sementes crioulas: resistência camponesa à colonização da vida no sudoeste do Paraná - Costa, Brendo Henrique da Silva (2023)
This dissertation seeks to understand the localized knowledge mobilized by the farmers of the Southwest of Paraná in their relations with the Creole seeds. Localized knowledge is produced and contextualized through specific experiences and situated in a given time and space. Seeds are crucial elements in food production and are closely linked to the knowledge and practices of the communities that grow them. These seeds, called in the region under study Creole seeds, result from knowledge accumulated over generations, which have adapted to climatic, ecological, and geographical conditions. The emergence of the colonial/modern world•system, from the fifteenth century onwards, promoted intense ruptures in the interactions between humans, seeds, and other living beings. Agricultural systems were simplified through the establishment of plantations, which instituted the commodification of plants, animals, and people, intensifying monocultures. As a result, Plantationocene emerges. With the Green Revolution, new configurations between agriculture and industry led multinational companies in the global north to control seeds. At the same time, farmers, indigenous peoples, and other traditional communities continued to advocate for using and reproducing their seeds and ways of doing agriculture. The research was developed through ethnography, emphasizing interviews, participant observation, and documentary analysis. Adopting the assumption of the so•called multispecies ethnography, this research was attentive to other beings associated with seeds and humans in this fabric of knowledge, namely, plants, animals, earth, water, microorganisms, etc. The research results demonstrate that the relationships established with Creole seeds overflow the cultivation and agriculture because they involve affections, exchanges between neighbors and families, collective recognition, and participation in festivals and seed fairs. In addition, farmers fear that these seeds will disappear due to the advance of conventional agriculture in the region, which makes intense use of transgenic seeds and pesticides, practices associated with the erosion of biodiversity. Thus, the research also points to future agendas, especially regarding conserving Creole seeds to protect sociobiodiversity and family•based agriculture since seeds can mobilize from food production to affection.